PERSPEKTIF SINTAKTIS TERHADAP PENGGUNAAN VOKATIF KOMBINASI BAHASA SUNDA DALAM KUMPULAN CERITA PENDEK KANYAAH KOLOT KARYA KARNA YUDIBRATA - Wahya; Pakpahan, Ferry Parsaulian (Jurnal Kajian Budaya dan Humaniora, 2024)
ABSTRACT This paper discusses Sundanese combination vocatives from a syntactic perspective, namely the first type of Sundanese combination vocative and the second type of sentence based on the syntactic form that contains Sundanese combination vocatives. This research uses a qualitative descriptive method. Presentation of data uses the listening method. Data analysis uses distributional methods with a syntactic approach. The research data source uses a written data source, namely a book collection of short stories entitled Kanyaah Kolot by Karna Yudibrata, 2014 edition. Based on the results of the analysis, it can be concluded that Sundanese combination vocatives can be classified into three types, namely (a) Type 1 Combination Vocatives of Kinship + Proper Names , (b) Type 2 Vocative Combination of Kinship + Government Position, (c) Type 3 Vocative Combination of Kinship + Religious Position, which consist of 9, 7 and 1 data respectively. Thus, Sundanese combination vocatives in the data source are dominated by Type 1 Vocative Combination of Kinship + Proper Name. Second, vocative Sundanese language combinations are found in four types of sentences based on their syntactic form, namely (a) declarative sentences, (b) imperative sentences, (c) argumentative sentences, and (d) exclamative sentences, which respectively contain 2, 5, 4, and 6 data. Thus, Sundanese vocative combinations tend to appear more often in exclamative sentences. In this exclamative sentence, there are two types of combination vocatives, namely Type 1 and Type 2. In this regard, Type 2 combination vocatives in Sundanese appear more often than Type 1 combination vocatives in that language. Key words: syntax, vocative, combination vocative, type, sentence type